The quality of nursing care regarding personal hygiene of patients admitted to a selected hospital in the Kavango region - A. van Dyk; L.F. Small; T. vd Merwe; M. Mueyu (AOSIS, 2004)
The aim of the study was to determine the quality of nursing care regarding personal hygiene of patients admitted to a hospital in the Kavango region of Namibia. The study was prompted by repeated media reports over the radio. Commentators and listeners expressed concern over the seeming lack of adequate hygienic measures, specifically with regard to patient care. To objectively quantify and describe the extent ot this problem, a single objective was stated, namely to measure the quality of nursing care with regard to patient hygiene. A descriptive survey design was chosen to explore and describe the problem. A check-list was developed to observe thirty patients (the total population) over a period of one week.